Steady-State Phosphorylation of Light-Harvesting Complex II Proteins Preserves Photosystem I under Fluctuating White Light(1)([W])([OA]) - Grieco, Michele (American Society of Plant Biologists, 2012)
According to the “state transitions” theory, the light-harvesting complex II (LHCII) phosphorylation in plant chloroplasts is essential to adjust the relative absorption cross section of photosystem II (PSII) and PSI upon changes in light quality. The role of LHCII phosphorylation upon changes in light intensity is less thoroughly investigated, particularly when changes in light intensity are too fast to allow the phosphorylation/dephosphorylation processes to occur. Here, we demonstrate that the Arabidopsis (Arabidopsis thaliana) stn7 (for state transition7) mutant, devoid of the STN7 kinase and LHCII phosphorylation, shows a growth penalty only under fluctuating white light due to a low amount of PSI. Under constant growth light conditions, stn7 acquires chloroplast redox homeostasis by increasing the relative amount of PSI centers. Thus, in plant chloroplasts, the steady-state LHCII phosphorylation plays a major role in preserving PSI upon rapid fluctuations in white light intensity. Such protection of PSI results from LHCII phosphorylation-dependent equal distribution of excitation energy to both PSII and PSI from the shared LHCII antenna and occurs in cooperation with nonphotochemical quenching and the proton gradient regulation5-dependent control of electron flow, which are likewise strictly regulated by white light intensity. LHCII phosphorylation is concluded to function both as a stabilizer (in time scales of seconds to minutes) and a dynamic regulator (in time scales from tens of minutes to hours and days) of redox homeostasis in chloroplasts, subject to modifications by both environmental and metabolic cues. Exceeding the capacity of LHCII phosphorylation/dephosphorylation to balance the distribution of excitation energy between PSII and PSI results in readjustment of photosystem stoichiometry.